The role of sea ice in the surface freshwater flux of the southern Weddell Sea: Insights from sea ice–ice shelf–ocean model simulations ... - Stulic, Lukrecia (Universität Bremen, 2024)
The strongest sea ice growth rates are found in coastal polynyas, where steady offshore winds promote divergent ice movement during the freezing season. The strong sea ice production on the southern Weddell Sea continental shelf leads to the densification of the near-surface waters, resulting in the formation of High Salinity Shelf Water (HSSW) that feeds the global overturning circulation and fuels the basal melt of vast Filchner-Ronne Ice Shelf (FRIS). The Finite Element Sea ice–ice shelf–Ocean Model (FESOM) forced by output from the regional atmospheric model COSMO-CLM (CCLM) with 14 km horizontal resolution is used in this thesis to investigate the role of sea ice for the surface freshwater flux of the southern Weddell Sea, with a particular focus on coastal polynyas. The presence of stationary icescape features (i.e. fast-ice areas and grounded icebergs) can influence the formation of polynyas and, therefore, impact sea ice production. The representation of the icescape in the model is included by ...